Neural regulation of N-cadherin gene expression in developing and adult skeletal muscle - Hahn, CG (J Neurosci, 1992)
Using monoclonal antibody and cDNA probes, we have studied N-cadherin gene expression in developing and adult chick skeletal muscle. N- cadherin was expressed by developing myotubes during the period of initial nerve-muscle contact but was downregulated within days of innervation. Treatment of embryos with d-tubocurare partially reversed this downregulation. In the adult, there were muscle fiber type differences in N-cadherin expression. N-cadherin was undetectable on normally innervated twitch fibers, while multiply innervated tonic muscle fibers expressed low but readily detectable levels of N- cadherin. Denervation led to the renewed expression of N-cadherin in twitch fibers as well as a marked increase in expression in tonic fibers. Levels of N-cadherin expressed by tonic fibers could also be modulated by animal housing conditions that favored either increased or decreased levels of daily motor activity. Increased motor activity was correlated with decreased levels of N-cadherin, while decreased motor activity correlated with increased levels of muscle N-cadherin. Results of in vitro studies using the calcium channel agonist ryanodine suggest that changes in intracellular calcium may be the initial signal linking neural stimulation with changes in muscle fiber expression of N- cadherin. Together, our results indicate that neural stimulation of chick skeletal muscle fibers dynamically and reversibly downregulates the expression of N-cadherin mRNA and protein. This pattern of regulation may be functionally important in limiting and/or promoting axon growth in innervated versus denervated muscle and may serve as a molecular model system for studies of the activity-dependent regulation of gene expression.